The Government’s Policy Strategy on Mitigating Covid-19 Pandemic In Indonesia - Kumba Digdowiseiso (Journal of Governance, 2022)
As one of the countries affected by the COVID-19 pandemic, Indonesia has a death toll of 7.8% of the total deaths due to the COVID-19 disease in the world. This figure is one of the highest death rates in the world. Of course, if it is not handled correctly, then various problems will continue to emerge from each other, so it can have a long-lasting bad impact if it is not appropriately handled. Therefore, the researcher intends to examine how the government will make economic policies in Indonesia to overcome the COVID-19 problem. This research will use a qualitative approach through the case approach method. The findings obtained from this research suggest that the government should make new economic policies to help various elements of society deal with the COVID-19 pandemic. These policies include reducing electricity and fuel costs, direct assistance in cash, issuing pre-employment cards and food cards for recipients, free examinations, and special incentives for medical staff.